Makna Qaşd as-Sabīl dalam Al-Qur’an: Analisis Semantik Toshihiko Izutsu - Alfirdaus, Rasya'; Ichwan, Moh. Nor; Pratama, Muhammad Yusuf (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to examine the interconnection of these meanings as a unified semantic structure using Toshihiko Izutsu’s Qur’anic semantic approach. This qualitative library research gathers data from tafsir works, Arabic dictionaries, and literature related to Izutsu’s semantic theory. The findings reveal that the basic meaning of qaşd as-sabīl is “the intended purpose of a path,” which, in its semantic relations, may refer to the straight path, salvation, guidance, Islamic law, and others. Historically, the meaning evolved from a general context (pre-Qur’anic), to more theological and specific (Qur’anic), and then to interpretive and contextual meanings (post-Qur’anic). The worldview behind this term shifted from general life purposes to the mission of conveying Islamic teachings. The diversity of interpretations is due to a structured relationship between its core meaning and its relational meanings shaped by semantic networks, historical context, and worldview constructions. Therefore, Izutsu’s semantic approach proves effective in revealing the complex and profound dimensions of qaşd as-sabīl in the Qur’an.